(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
It highlights the role and importance of marketing in attracting investment and their role in economic development, and the article also outlines the existing problems in attracting foreign investment in the national economy and what measures should be taken to activate their prevention.